THE INFLUENCE IMPLEMENTATION MODEL SELF DIRECTED LEARNING TOWARDS ABILITY THINK CRITICAL CHILDREN AGE 5-6 YEAR - Hasbur, Heni Safitri; Intisari; Hajerah; Sadaruddin (PRATAMA WIDYA : Jurnal Pendidikan Anak Usia Dini, 2024)
This research is a quasi-experimental research with a design Nonequivalent-Groups Pretest- Posttest Design which aims to determine the influence of the application of self-directed learning models learning on critical thinking skills in children aged 5-6 years at the Al-Hanif Muta'awin Integrated Islamic PAUD. The population studied were all children in group B at the PAUD, with a total of 40 children. The research sample consisted of group B1 as an experimental class with 15 children, and group B2 as a control class with the same number. Data collection methods used included descriptive analysis and inferential analysis. The results of the study showed that there was a significant effect of the application of the self-directed learning model on the critical thinking skills of children aged 5-6 years. The test results showed an increase in critical thinking skills in the experimental group, with an average value reaching 20.20, while in the control group the average value was 13.67. The difference in average values between the two groups showed that the experimental group had a higher value. Thus, based on the results of the Wilcoxon test, it can be concluded significantly that the application of the self-directed learning model has an effect on critical thinking skills in children aged 5-6 years at the Al-Hanif Muta'awin Integrated